2016
DOI: 10.1002/slct.201600042
|View full text |Cite
|
Sign up to set email alerts
|

Furanolabdanoid–based 1,2,4‐oxadiazoles: Synthesis and cytotoxic activity

Abstract: Several 15,16-epoxy-8,13,14-labdatriene derivatives modified at the C-16 position with a 1,2,4-oxadiazole ring with various substituent in the 5-th position, were obtained via multistep synthesis from 16-formyl derivatives of natural diterpenoid lambertianic acid. The cytotoxicity of furanolabdanoid-based 1,2,4oxadiazoles was evaluated against human cancer cells (CEM-13, MT-4, U-937, MCF-7, MDA-MB-231, MEL-8) using the conventional MTT assays. All the tested diterpenoid-oxadiazole hybrids displayed better cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…From this screening, compound 55 ( Figure 10) emerged for its remarkable toxicity, with GI50 values of 0.08 ± 0.03 µM on CEM-13, and 0.35 ± 0.11 µM on MT-4. Moreover, cytofluorimetric analysis demonstrated that treatment of U937 cells with 55 induced apoptosis in 46.8% of cells after 24 hours and 84.4% after 48 hours [91].…”
Section: Oxadiazoles Derivatives As Anticancer Agents Without a Specimentioning
confidence: 96%
See 2 more Smart Citations
“…From this screening, compound 55 ( Figure 10) emerged for its remarkable toxicity, with GI50 values of 0.08 ± 0.03 µM on CEM-13, and 0.35 ± 0.11 µM on MT-4. Moreover, cytofluorimetric analysis demonstrated that treatment of U937 cells with 55 induced apoptosis in 46.8% of cells after 24 hours and 84.4% after 48 hours [91].…”
Section: Oxadiazoles Derivatives As Anticancer Agents Without a Specimentioning
confidence: 96%
“…Modification of oxadiazole scaffolds through conjugation to bioactive natural products, also represent a promising approach. Mironov et al exploited Furano-diterpenoids of the labdane series, an anti-inflammatory and anti-allergic drug-like [90], to build novel and potent derivatives [91]. In detail, 1,2,4-oxadiazoles were conjugated to labda-8(9),13,15-triene or labda-8(17),13,15-triene core and their antiproliferative activity and GI50 on CEM-13, MT-4 and U937 cells were measured [91].…”
Section: Oxadiazoles Derivatives As Anticancer Agents Without a Specimentioning
confidence: 99%
See 1 more Smart Citation
“…Modification of oxadiazole scaffolds through conjugation to bioactive natural products also represents a promising approach. Mironov et al exploited Furano-diterpenoids of the labdane series, an anti-inflammatory and anti-allergic drug-like [ 90 ], to build novel and potent derivatives [ 91 ]. In detail, 1,2,4-oxadiazoles were conjugated to labda-8(9),13,15-triene or labda-8(17),13,15-triene core and their antiproliferative activity and GI 50 on CEM-13, MT-4 and U937 cells were measured [ 91 ].…”
Section: Oxadiazoles Derivatives As Anticancer Agents Without a Spmentioning
confidence: 99%
“…Mironov et al exploited Furano-diterpenoids of the labdane series, an anti-inflammatory and anti-allergic drug-like [ 90 ], to build novel and potent derivatives [ 91 ]. In detail, 1,2,4-oxadiazoles were conjugated to labda-8(9),13,15-triene or labda-8(17),13,15-triene core and their antiproliferative activity and GI 50 on CEM-13, MT-4 and U937 cells were measured [ 91 ]. From this screening, compound 55 ( Figure 10 ) emerged for its remarkable toxicity, with GI 50 values of 0.08 ± 0.03 µM on CEM-13, and 0.35 ± 0.11 µM on MT-4.…”
Section: Oxadiazoles Derivatives As Anticancer Agents Without a Spmentioning
confidence: 99%